CD161-expressing human T cells. - Fergusson, JR; Fleming, V; Klenerman, P (2011)
Expression of the Natural Killer cell receptor CD161 has recently been identified on a subset of T cells, including both CD4+ T helper and CD8+ T cells. Expression of this molecule within the adult circulation is restricted to those T cells with a memory phenotype. However, the distinct properties of these T cell populations is yet to be fully determined, although expression of CD161 has been related to the secretion of interleukin-17, and therefore to a type 17 phenotype. Recent studies have aimed to determine both the origin of these cells and the significance of CD161 expression as either a marker of specific cell types or as an effector and regulator of lymphocyte function, and hence to characterize the role of these CD161+ cells within a variety of human diseases in which they have been implicated.